(untitled) (Research, Society and Development, 2022)
Objective: Investigate non-adherence to the drug treatment for multidrug-resistant tuberculosis (MDR TB). Methodology: A literature searching was carried out in databases, Lilacs and Medline, using the following descriptors: ‘Tuberculose Resistente a Múltiplos Medicamentos’, ‘Tuberculose Multidroga Resistente’, ‘Tuberculose Farmacorresistente’, ‘Tuberculosis’, ‘Multidrug-Resistant’, ‘Tuberculosis Resistente a Múltiples Medicamentos’, ‘Adesão à Medicação’, ‘Adesão’, ‘Medication Adherence’ e ‘Cumplimiento de la Medicación’. The period selected for the research was December 2016 to December 2021. After applying the adopted criteria, 18 articles met the prerequisites for the analysis. Results: The treatment abandonment rate in TB is high and one of the main concerns for TB control is the reduction of this non-adherence to drug therapy. The factors that provide better treatment adherence are related to health care, TB control programs, in addition to the patients’ desire to live. Conclusion: MDR TB is a major public health problem, requiring the application of several measures related to patient care by the multidisciplinary health team.